2014
DOI: 10.1016/j.pharmthera.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and therapeutic role of inorganic nitrite and nitrate in vasodilatation

Abstract: Nitrite has emerged as an important bioactive molecule that can be biotransformed to nitric oxide (NO) related metabolites in normoxia and reduced to NO under hypoxic and acidic conditions to exert vasodilatory effects and confer a variety of other benefits to the cardiovascular system. Abundant research is currently underway to understand the mechanisms involved and define the role of nitrite in health and disease. In this review we discuss the impact of nitrite and dietary nitrate on vascular function and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 214 publications
(236 reference statements)
0
36
0
1
Order By: Relevance
“…The nitrate–nitrite–NO pathway has been shown to regulate blood pressure and hypoxic vasodilatation and improve exercise performance and mitochondrial efficiency (Bailey et al ., 2014). Our work and those of others have demonstrated that infusions of sodium nitrite in healthy subjects dilate forearm vasculature, with significant potentiation during hypoxia, thereby preferentially dilating capacitance vessels (Maher et al ., 2008; van Faassen et al ., 2009; Totzeck et al ., 2012; Kapil et al ., 2014).…”
Section: A Novel Therapeutic Pathway: Nitrate–nitrite–nomentioning
confidence: 99%
“…The nitrate–nitrite–NO pathway has been shown to regulate blood pressure and hypoxic vasodilatation and improve exercise performance and mitochondrial efficiency (Bailey et al ., 2014). Our work and those of others have demonstrated that infusions of sodium nitrite in healthy subjects dilate forearm vasculature, with significant potentiation during hypoxia, thereby preferentially dilating capacitance vessels (Maher et al ., 2008; van Faassen et al ., 2009; Totzeck et al ., 2012; Kapil et al ., 2014).…”
Section: A Novel Therapeutic Pathway: Nitrate–nitrite–nomentioning
confidence: 99%
“…Работами групп F.J. Larsen [58][59][60] и S.J. Bailey [9,10] было найдено, что про-исходит уменьшение расхода кислорода в работа-ющих мышцах при физическом упражнении после краткосрочного добавления нитрата в диету у здо-ровых лиц. Приведем рассуждения F.J. Larsen et al [59] вместе со ссылками, которые дают авторы: «Этот эффект был большой неожиданностью, пото-му что классическая физиология упражнений пред-писывает минимальные колебания расхода кисло-рода на определенной рабочей нагрузке для любого лица, уровня тренированности [70], возраста или диеты [7].…”
Section: No изменяет эффективность окислительного фосфорилированияunclassified
“…An abundance of research has focused on defining the vasoactive/cardioprotective roles of NO 2 À with many studies suggesting that the reduction of NO 2 À to NO compliments the well-understood NOS pathway of NO production, particularly when NOS function becomes uncoupled or otherwise impaired (reviewed by 34,35 ). The vascular responses to NO 2 À infusion presented herein support this notion.…”
Section: Effects Of Inorganic No 2 à Infusion On Skeletal Muscle Bf Amentioning
confidence: 99%